2017 ORNAC National Conference Abstracts - ORNAC, ORNAC (Operating Room Nurses Association of Canada Journal, 2019)
The ORNAC National Conference offers many opportunities for the sharing of experiences and results among perioperative nurses across Canada. The following abstracts were share in 2017 and outline various contributions of OR Nurses to the advancement of their profession or improvements in their workplace. Some were later expanded in to articles in the ORNAC Journal. Watch for more of this perioperative ingenuity in 2019 and consider what advancements or ideas you bring to your workplace and profession that could be shared with your peers through the ORNAC Journal or at conference.